EDUKASI KONVERSI HASIL PENELITIAN MENJADI KARYA PUBLIKASI PENGABDIAN KEPADA MASYARAKAT - Sudarnice Sudarnice; La Sudarman; Wa Ode Sitti Budiaty; Sri Wahyuni; Niska Salsiani Sinta; Hilda Sulistia Alam (LPPM ITB AAS Indonesia Surakarta, 2024)
The aim of this community service is to provide knowledge about how to make lecturer research results into community service results that are published in the National Journal indexed by Sinta. The service method used is an educational method with systematic implementation steps in the form of: activity preparation stage, activity implementation stage, activity evaluation and mentoring stage. After carrying out this service program, it is hoped that the participants will have the knowledge and expertise in converting research results into community service work published in the National Journal indexed by Sinta.